Information Exchange, Market Transparency and Dynamic Oligopoly - Per Baltzer Overgaard; Peter Møllgaard (Copenhagen Business School (CBS), Department of Economics, 2006)
In the economics literature, various views on the likely (efficiency) effects of information exchange, communication between firms and market transparency present themselves. Often these views on information flows are highly conflicting. On the one hand, it is argued that increased information dissemination improves firm planning to the benefit of society (including customers) and/or allows potential customers to make the right decisions given their preferences. On the other hand, the literature also suggests that increased information dissemination can have significant coordinating or collusive potential to the benefit of firms but at the expense of society at large (mainly, potential customers). In this chapter, we try to make sense of these views, with the aim of presenting some simple lessons for antitrust practice. In addition, the chapter presents some cases, from both sides of the Atlantic, where informational issues have played a significant role.
hdl:10398/7533
Keywords: H00; 330